Protocadherin 7 inhibits cell migration and invasion through E-cadherin in gastric cancer - Hong-Fang Chen; Ran-Ran Ma; Jun-Yi He; Hui Zhang; Xiao-Ling Liu; Xiang-Yu Guo; Peng Gao (Tumor Biology)
The protocadherin 7 is a member of the protocadherin family that expressed aberrantly in many types of human cancers. However, its expression, function, and underlying mechanisms are little known in gastric cancer. In this study, we detected protocadherin 7 expression in gastric cancer tissues and non-tumorous gastric mucosa tissues by real-time quantitative polymerase chain reaction and immunohistochemistry. The association of protocadherin 7 expression with the clinicopathological characteristics and the prognosis was subsequently analyzed. MTS ((3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium)) and transwell assays were performed to assess the effect of protocadherin 7 on proliferation, migration, and invasion in gastric cancer cell lines. Moreover, real-time quantitative polymerase chain reaction and western blot were used to detect the expression of epithelial–mesenchymal transition markers. Protocadherin 7 expression was decreased gradiently from normal tissue to gastric cancer, especially in gastric cancer tissue with lymph node metastasis. Low expression of protocadherin 7 was significantly associated with Lauren’s classification ( p  = 0.0005), lymph node metastases ( p  = 0.0002), and tumor node metastasis stage ( p  = 0.0221), as well as poor prognosis ( p  < 0.05). Furthermore, down-regulation of protocadherin 7 in gastric cancer cell lines significantly increased their migration and invasion abilities (both p  < 0.05), while it had no influence on the gastric cancer cell proliferation ( p  > 0.05). Additionally, our results demonstrated that E-cadherin expression was down-regulated in gastric cancer cells with protocadherin 7 depletion. Our data indicated that protocadherin 7 may play important roles in the invasion and metastasis of gastric cancer, and protocadherin 7 could suppress cell migration and invasion through E-cadherin inhibition. Protocadherin 7 can serve as a novel biomarker for diagnostic and prognosis in patients with gastric cancer.